2008
DOI: 10.1177/1545968308315996
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Balance After Stroke With Multisensorial Training: A Single-Blind Randomized Controlled Study

Abstract: No evidence was found for the superiority of a multisensorial rehabilitation program in ambulatory patients with impairments beyond the time of inpatient therapy. Additional studies are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 38 publications
1
50
0
6
Order By: Relevance
“…The results illustrate that the agility exercise would be beneficial in reducing falls in chronic stroke patients who have altered motor coordination. Yelnik et al (2008) randomized 68 patients who had experienced a recent stroke but had reached the chronic recovery period (average of 7 months postevent). The experimental group (n = 33) patients received multisensorial training, and the control group (n = 35) received neurodevelopmental theory-based treatment for 1 hour, 5 days a week, for 4 weeks.…”
Section: Aerobic Exercises To Improve Balancementioning
confidence: 99%
“…The results illustrate that the agility exercise would be beneficial in reducing falls in chronic stroke patients who have altered motor coordination. Yelnik et al (2008) randomized 68 patients who had experienced a recent stroke but had reached the chronic recovery period (average of 7 months postevent). The experimental group (n = 33) patients received multisensorial training, and the control group (n = 35) received neurodevelopmental theory-based treatment for 1 hour, 5 days a week, for 4 weeks.…”
Section: Aerobic Exercises To Improve Balancementioning
confidence: 99%
“…Twelve of these studies were experimental designs (RCTs/one prospective parallel group design) [10,[26][27][28][29][30][31][32][33][34][35][36], while five studies used an N-of-1/case report design to describe clinical practice with respect to a specific client/clients, with study design varying from a case report [37,38], to a case series, to a more sophisticated single subject research design (SSRDs) [40,41]. One other paper was a systematic review [11].…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] Hence to address this deficits of sensorimotor integration adaptation of regular physical therapy exercises with the use of vision and surface input manipulations along with sensory conflict conditions to challenge balance has shown to have positive effects on balance recovery. 17 Recent studies have shown that exercise interventions in the form of task oriented exercises which are intended to reinforce the relationship between training and functional performance, such as exercises in sitting, standing, walking and stair climbing as a strategy to improve balance and functional mobility in stroke patients. [18][19][20] Bayouk et al, in their study, found that task oriented balance training with altered sensory input shows significant improvement in standing balance in chronic stroke patients.…”
Section: Introductionmentioning
confidence: 99%